Facile synthesis and enhanced microwave absorption properties of anthracite-based carbon/Ni3Fe/NiO ternary composites. (6th August 2020) - Ren, Hengdong; Ma, Jialin; Zhou, Jun; Shu, Xiangfeng; Liu, Zhenying; Liu, Yin; Zhao, Yan; Ge, Tao; Min, Fanfei; Kong, Ling Bing
Abstract : A low-frequency microwave absorber was synthesized by using a microwave radiation method. Abstract : Anthracite-based carbon/Ni3 Fe/NiO ternary composites were synthesized by using a microwave radiation method at a frequency of 915 MHz. Phase and elemental compositions of the composites were investigated by X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). According to FESEM observations, Ni3 Fe and NiO particles are uniformly implanted into grid-like porous structures and interlayers on the surface of anthracite-based carbon. The carbonization was realized at 700 °C, which could be attributed to the presence of a large number of polar molecules in anthracite that responded actively to microwave irradiation. The oxygen-containing functional groups in anthracite-based carbon provide multiple relaxation processes. Therefore, the composites exhibited a minimum reflection loss of −51.66 dB at 5.52 GHz, with effective absorption covering the S and C bands. Importantly, this result shows a facile method for preparing coal-based carbon/magnetic powder, which utilizes the rapid reaction of microwave radiation.